"MOSQUITO FAUNA OF IRAN (DIPTERA: CULICIDAE) 3- CULISETA, COQUILLETTIDIA, URANOTAENIA " - M. Zaim; AV.Manouchehri; MRY.Ershadi (Tehran University of Medical Sciences, 1986)
In the previous studies by foreign investigators on Culicinae fauna of Iran two Culiseta, Cs. Longiareolata and Cs. annulata; one Coguillettidia, Cog. richiardii, and one Uranotaenia species, Ur. unguiculata have been reported. In the comprehensive study of the Culicinae fauna of Iran, made by the School of Public Health, Teheran University, since 1980, not only all named species, except one, were recollected, but two additional species were also captured which formerly have not been known to occur in Iran. These are Cs. alaskaensis and an unnamed, new species of Coquillettidea. Coq. richiardii has not been collected in Iran since the presence of 31 species of Culicinae in Iran. Spatial distribution of each species is presented.